The story of rock - Sagar, Lindsey (San Diego, CA : Silver Dolphin Books, an imprint of Printers Row Pub. Group, 2018)
Simple text and color illustrations introduce young readers to rock music and musicians including Elvis Presley, Chuck Berry, Janis Joplin, David Bowie, and more.
"Perfect for baby rockers"--Front cover.
Cover title.
On board pages.
1.8
Preschool.
Preschool
Keywords: Board books -- Specimens; Rock music -- Juvenile literature; Rock musicians -- Juvenile literature; Board books; Rock music; Rock musicians; Board books for children; Rock music; Rock musicians